2016
DOI: 10.1109/jestpe.2016.2544789
|View full text |Cite
|
Sign up to set email alerts
|

Grid-Connected PV-Wind-Battery-Based Multi-Input Transformer-Coupled Bidirectional DC-DC Converter for Household Applications

Abstract: In this project, a control strategy for power flow management of a grid-connected hybrid PV-wind-battery based system with an efficient multi-input transformer coupled bidirectional dc-dc converter is presented. The proposed system aims to satisfy the load demand, manage the power flow from different sources, inject surplus power into the grid and charge the battery from grid as and when required. A transformer coupled boost half-bridge converter is used to harness power from wind, while bidirectional buck-boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(66 citation statements)
references
References 40 publications
0
66
0
Order By: Relevance
“…A dual input DC-DC converter is used for simultaneous maximum power point tracking control (MPPT) of a solar PV generation system consisting of photovoltaic (PV) panels and battery, operation and control of this topology is given in [21,22], In this paper DC-DC converter is shown in Fig. 3, with Solar and battery inputs is considered for power transfer from PV and Battery to load/Grid and its working is explained in three modes.…”
Section: Principle Of Operation Of Convertermentioning
confidence: 99%
See 1 more Smart Citation
“…A dual input DC-DC converter is used for simultaneous maximum power point tracking control (MPPT) of a solar PV generation system consisting of photovoltaic (PV) panels and battery, operation and control of this topology is given in [21,22], In this paper DC-DC converter is shown in Fig. 3, with Solar and battery inputs is considered for power transfer from PV and Battery to load/Grid and its working is explained in three modes.…”
Section: Principle Of Operation Of Convertermentioning
confidence: 99%
“…Active and reactive power reference based load sharing, conventional droop control and MPPT based droop control are proposed to extract power from DGs and send to load/grid, but here PV and storage are considered independently [18][19][20]. A multi-input transformer coupled bidirectional DC-DC converter is proposed in [21][22][23][24], here DC voltage regulation is taken care by Inverter in grid-connected mode. But in Islanded mode of operation, battery and DC-DC converter have to look out and PV is forced to operate in non-MPPT mode to maintain voltage regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Being the two fastest growing sources of power generation from renewable energy sources, several studies have shown the benefits (the complimentary nature of solar irradiance and wind speed [195][196][197][198]) of hybrid generation from a mix of renewable energy sources such as wind and PV systems [199]. Other distributed energy resources (DERs), such as battery energy storage [200] and most recently tidal [201], have been proposed as part of a composite hybrid system to address the challenges of power generation from PV systems alone.…”
Section: Optimal MIX and Dispatch Of Renewable Energy Sourcesmentioning
confidence: 99%
“…The basic philosophy and preliminary study of a compact and low-cost multi-input transformer-coupled dcdc converter capable of interfacing multiple sources for a stand-alone application is presented in [10]. In [11], the integration of renewable sources to the grid, detailed analysis, exhaustive simulation have been included.…”
Section: Battery Based Grid Connectedmentioning
confidence: 99%